2001
DOI: 10.1002/hed.10031
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment for and outcomes of mandibular conservation surgery

Abstract: Mandibular conservation surgery is oncologically safe for patients with early mandibular invasion. Accurate preoperative assessment that combines clinical examination and radiographic evaluation is better than either modality alone, but clinical judgment is still necessary for proper patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
1
27
1
2
Order By: Relevance
“…The prognoses for SCC of the tonsil, floor of mouth, alveolar ridge, and RMT differ drastically despite each anatomic unit being separated by only millimeters [1][2][3]. Surgery is technically demanding since the tumor has often extended to adjacent sites at the time of diagnosis, and complete removal frequently requires resection and reconstruction of the mandible, oral mucosa, oropharynx and even the maxilla [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The prognoses for SCC of the tonsil, floor of mouth, alveolar ridge, and RMT differ drastically despite each anatomic unit being separated by only millimeters [1][2][3]. Surgery is technically demanding since the tumor has often extended to adjacent sites at the time of diagnosis, and complete removal frequently requires resection and reconstruction of the mandible, oral mucosa, oropharynx and even the maxilla [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Few authors have reported adequate tumor control with marginal mandibulectomy for superficial medullary cavity involvement in a limited number of cases. 3,11 In our series, 1 patient with evidence of superficial medullary invasion achieved good tumor control after marginal mandibulectomy and postoperative radiotherapy. Nevertheless, we recommend segmental resection when tumor invades the medullary cavity.…”
Section: Discussionmentioning
confidence: 93%
“…Although bone invasion is thought to be a poor prognostic factor of tumor control by some, 8,10,11 other authors have varying opinions. 3,4,12 In our series, the local recurrence rate was 14.3% in the mandibular bone invasion group and 22.2% in the no mandibular bone invasion group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tanıda, endoskopik bakıdan ve görüntüleme yöntem-lerinden faydalanılır ve fizik bakıda dil palpasyonu, tümör boyutlarının ve sertliğinin saptanması açısından büyük önem taşır. Bilgisayarlı Tomografi ve Manyetik Rezonans görüntüleme ile tümör boyutları ve invazyonu, mandibular tutulum ve servikal lenf metastazı değerlendirilir (7,8).…”
Section: Gereç Ve Yöntemunclassified